Porphyrin Antennas on Carbon Nanodots: Excited State Energy and Electron Transduction - Arcudi, Francesca; Strauß, Volker; Dordevic, Luka; Cadranel, Alejandro; Guldi, Dirk Michael; Prato, Maurizio (Angewandte Chemie International Edition, 2017)
We report the synthesis and electron donor-acceptor features of a novel nanohybrid, in which the light-harvesting and electron-donating properties of a meso-tetraarylporphyrin (TArP) are combined with the electron-accepting features of nitrogen-doped carbon nanodots (NCNDs). In particular, in an ultrafast process (>1012 s-1), visible-light excitation transforms the strongly quenched porphyrin singlet excited states into short-lived (225 ps) charge-separated states. On the other hand, ultraviolet light excitation triggers a non-resolvable transduction of singlet excited state energy from the NCNDs to the porphyrins, followed by the same charge separation observed upon visible light excitation.
EAM Import::2019-03-08